Preoperative prediction of lymphovascular invasion and T-staging of rectal cancer via a dual-energy computed tomography iodine map: a feasibility study - Jinliang Zhang; Hui Qi; Chun Yang; Ling Liu; Yuxin Wang; Wei Li (Diagnostic and Interventional Radiology)
PURPOSE: To investigate the value of dual-energy computed tomography (DECT) in predicting lymphovascular invasion (LVI) and the accuracy of preoperative T-staging of rectal cancer (RC). METHODS: Forty-nine patients with RC who had not received radiotherapy were enrolled to undergo a DECT scan. All patients underwent surgical tumor resection within 3–5 days after the DECT scan. Preoperative T-staging of RC based on images was performed by experienced radiologists. The normalized iodine concentrations (NIC) of the tumor and the perirectal adipose tissue (PAT) from the arterial phase (AP) and venous phase (VP) were measured using DECT. The tumor LVI and T-staging confirmed by pathology were used as the gold standard for grouping (group A, LVI−; group B, LVI+; group C, T1-2; and group D, T3-4a). The NIC values between two groups were compared using the Mann–Whitney U test, with P < 0.05 indicating a statistically significant difference. The accuracy of NIC in predicting LVI and distinguishing T1-2 RC from T3-4a RC were determined via receiver operating characteristic curve analysis, and the optimal cut-off of NIC was determined using the area under the curve. RESULTS: The tumor NIC values were significantly higher in the LV+ group than in the LVI− group in the VP (0.728 ± 0.031 vs. 0.669 ± 0.034, P < 0.001). The NIC values of PAT were significantly higher in the T3-4a group than in the T1-2 group in both the AP (4.034 ± 0.991 vs. 3.115 ± 0.581, P < 0.05) and the VP (5.481 ± 1.054 vs. 3.450 ± 0.980, P < 0.001). The accuracy of using NIC values to distinguish between the LVI+ group and the LVI− group and to diagnose the T3-4a group were 85.7% and 89.8%, respectively. However, there was no statistically significant difference between the NIC value in the LVI+ group and in the LVI− group in the AP. There was also no statistical difference in the tumor NIC value between the T1-2 group and the T3-4a group. CONCLUSION: The tumor and PAT NIC are valuable indicators in RC that can preoperatively predict LVI and improve the accuracy of preoperative RC T-staging. CLINICAL SIGNIFICANCE: The use of DECT improves the T-staging and LVI prediction of RC, which is helpful in guiding the clinical selection of appropriate treatment modalities and improving prognostic outcomes.